Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To determine which equation models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds, we need to find an equation that satisfies the conditions provided: the weight is 9 inches below equilibrium at [tex]\( t = 0 \)[/tex] and returns to this position after [tex]\( t = 3 \)[/tex] seconds.
Given equations:
1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
Let's test each equation separately:
### 1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 3 \right) = -9 \cos(\pi) = -9 \times -1 = 9 \][/tex]
This does not match the condition at [tex]\( t = 3 \)[/tex] since we need [tex]\( d = -9 \)[/tex].
### 2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 3 \right) = -9 \cos(2\pi) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 3 \)[/tex].
### 3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
### 4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{2\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
Only the second equation [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex] satisfies the condition both at [tex]\( t = 0 \)[/tex] and [tex]\( t = 3 \)[/tex] seconds. Thus, the correct equation that models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds is:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} t \right) \][/tex]
Given equations:
1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
Let's test each equation separately:
### 1. [tex]\( d = -9 \cos \left( \frac{\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{\pi}{3} \times 3 \right) = -9 \cos(\pi) = -9 \times -1 = 9 \][/tex]
This does not match the condition at [tex]\( t = 3 \)[/tex] since we need [tex]\( d = -9 \)[/tex].
### 2. [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 0 \right) = -9 \cos(0) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 0 \)[/tex].
At [tex]\( t = 3 \)[/tex]:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} \times 3 \right) = -9 \cos(2\pi) = -9 \times 1 = -9 \][/tex]
This satisfies the condition at [tex]\( t = 3 \)[/tex].
### 3. [tex]\( d = -3 \cos \left( \frac{\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
### 4. [tex]\( d = -3 \cos \left( \frac{2\pi}{9} t \right) \)[/tex]
At [tex]\( t = 0 \)[/tex]:
[tex]\[ d = -3 \cos \left( \frac{2\pi}{9} \times 0 \right) = -3 \cos(0) = -3 \times 1 = -3 \][/tex]
This does not match the condition at [tex]\( t = 0 \)[/tex].
Only the second equation [tex]\( d = -9 \cos \left( \frac{2\pi}{3} t \right) \)[/tex] satisfies the condition both at [tex]\( t = 0 \)[/tex] and [tex]\( t = 3 \)[/tex] seconds. Thus, the correct equation that models the distance [tex]\( d \)[/tex] of the weight from its equilibrium after [tex]\( t \)[/tex] seconds is:
[tex]\[ d = -9 \cos \left( \frac{2\pi}{3} t \right) \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.